2016
DOI: 10.2337/db16-0341
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Bypass Reduces Symptoms and Hormonal Responses in Hypoglycemia

Abstract: Gastric bypass (GBP) surgery, one of the most common bariatric procedures, induces weight loss and metabolic effects. The mechanisms are not fully understood, but reduced food intake and effects on gastrointestinal hormones are thought to contribute. We recently observed that GBP patients have lowered glucose levels and frequent asymptomatic hypoglycemic episodes. Here, we subjected patients before and after undergoing GBP surgery to hypoglycemia and examined symptoms and hormonal and autonomic nerve responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
68
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 38 publications
14
68
1
3
Order By: Relevance
“…The response of glucagon to hypoglycaemia was attenuated before reversal, which is in accordance with a recent observation of reduced symptoms and counter-regulatory hormonal response to hypoglycaemia after RYGB surgery [10]. All subjective symptoms of hypoglycaemia disappeared, and we observed relief of biochemical hypoglycaemia associated with a 'reversed' hormone profile, with significantly reduced insulin and GLP-1 responses combined with a decreased insulin clearance after reversal.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The response of glucagon to hypoglycaemia was attenuated before reversal, which is in accordance with a recent observation of reduced symptoms and counter-regulatory hormonal response to hypoglycaemia after RYGB surgery [10]. All subjective symptoms of hypoglycaemia disappeared, and we observed relief of biochemical hypoglycaemia associated with a 'reversed' hormone profile, with significantly reduced insulin and GLP-1 responses combined with a decreased insulin clearance after reversal.…”
Section: Discussionsupporting
confidence: 91%
“…Concentrations of GIP and ghrelin were enhanced after reversal. The response of glucagon to hypoglycaemia was attenuated before reversal, which is in accordance with a recent observation of reduced symptoms and counter-regulatory hormonal response to hypoglycaemia after RYGB surgery [10]. Notably, peripheral insulin sensitivity (measured as glucose disposal during hyperinsulinaemic-euglycaemic clamps) remained unchanged despite weight gain.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, texture had an effect on GLP-1 and on glucose in spite of its absence of effect on insulin. It is possible that the suppression of glucagon release by GLP-1 [35] proportional to the magnitude of the GLP-1 release, and/or a defect in other counter regulatory hormones [36], favored lower blood glucose levels after the liquid meal. However, these counter-regulatory hormones were not measured in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we also found that patients with lower blood glucose levels tend to present later. Recent studies suggest that bariatric surgery can lead to an attenuated counter-regulatory hormone response to hypoglycemia and that there are many bariatric surgery patients with asymptomatic hypoglycemia [14, 17]. It is possible that these patients have some level of hypoglycemic unawareness so only developed symptoms at more extreme levels of hypoglycemia, and therefore had delayed presentation of PBSH.…”
Section: Discussionmentioning
confidence: 99%
“…A 2015 survey-based study found that PBSH may affect up to one third of patients while a nationwide Swedish cohort study showed that only 0.2% of patients undergoing roux-en-Y gastric bypass (RYGB) required hospitalization for PBSH [12, 13]. Early investigators suggested pancreatic nesidioblastosis with resultant hyperinsulinemia as the underlying cause, but further work has shown that PBSH is the result of a multifaceted alteration in glucose homeostasis [11, 14]. Recent studies have identified several risk factors for the development of PBSH such as lower preoperative glycated hemoglobin (A1C) and body mass index (BMI) as well as greater postoperative weight loss [15, 16].…”
Section: Introductionmentioning
confidence: 99%